Learning PHP Data Objects: A Beginner’s Guide to PHP Data Objects, Database Connection Abstraction Library for PHP 5 - Popel, Dennis (Packt Publishing, 2011)
This book starts with an overview of PHP Data Objects (PDO), followed by getting started with PDO. Then it covers error handling, prepared statements, and handling rowsets, before covering advanced uses of PDO and an example of its use in an MVC application. Finally an appendix covers the new object-oriented features of PHP 5. This book will guide you through the data layer abstraction objects in PHP. PHP developers who need to use PDO for data abstraction.